Evaluation of Community Perception, Vegetation Structure and Composition, and Economic Value of Community Forests Based on A Dynamic Model System in Agroforestry Land: (Case Study in Babadan Village, Ngajum District, Malang Regency) - Satrio Deny Setyawan (Journal Of Social Science (JoSS), 2026)
The management of community forests in the Babadan area is still relatively low, because judging from the survey, many are managed individually. The importance of cooperation between other parties with new knowledge will be able to foster good forest management. The purpose of this study is to analyze and describe the relationship between community perception and community forests. The research was carried out on community land in Ngajum District, Malang Regency, East Java as the location for determining community forests in July 2024. Location determination is based on observations, studies and literature studies. This study uses a likert scale with categories and rating scales to determine the social and economic perception of the community. Vegetation analysis was carried out to calculate vegetation types as a step to obtain data on the distribution of community forest composition with the knowledge of important value and diversity indexes, then economic valuation analysis was carried out to analyze community forest income. Then the integration of the model in all elements with the community's economy is carried out, to find out how the income will be for the next 20 years. The results of the study showed that the perception of the community in Babadan Hamlet towards the community forest was high (62-70%). One of the sample lands had 1,585 trees with an average importance index of 300 and the highest diversity index of 1,960, dominated by mahogany,